Analisis Cluster Vaksinasi Covid-19 Dengan Mempertimbangkan Jumlah Permintaan Menggunakan Metode K-Means Clustering di Kabupaten Karawang - Liana Liana; Winarno Winarno; Rizki Achmad Darajatun (Universitas Kadiri, 2022)
Since January 2020 Indonesia is affected by the pandemic of Covid-19. Immunization is the quite possibly the best endeavors to defeat the Covid-19 pandemic, which is as yet on going Currently the number of people who come for vaccination is increasing. However, there are several sub-districts that have relatively far distances from the vaccination sites determined by the government, so it is necessary to group several sub-districts into several clusters, with the aim of forming additional vaccination points by dividing the area into several locations so that they are easily accessible by the entire community of Karawang district. The examination was led utilizing an unmistakable quantitative technique with the wellspring of the information utilized in this investigation obtained from website : Covid-19 task force in the Karawang area. The information utilized in this investigation is information on June 18, 2021 which comprises of 30 locale. The technique utilized is the K-Means Clustering strategy which is prepared utilizing the SPSS 23 programming and accepts that the interest for each sub-locale is drawn closer with a positive number of Covid-19 in that sub-area. The consequences of the examination show that the sub-areas in cluster1 have 1-sub-locale, in group 2 there are 9 sub-regions and in bunch 3 there are 11 sub-regions. Negara Kepulauan Republik Indonesia terdampak pandemi Covid-19 sejak Januari 2020. Vaksinasi adalah salah satu solusi terbaik saat ini untuk melindungi dari pandemi Covid-19. Saat ini jumlah masyarakat yang datang untuk vaksinasi semakin meningkat. Namun terdapat beberapa kecamatan yang memiliki jarak relatif jauh dari tempat vaksinasi yang ditentukan oleh pemerintah, sehingga perlu dilakukan pengelompokkan beberapa kecamatan menjadi beberapa cluster, dengan tujuan membentuk tambahan titik vaksinasi dengan cara membagi wilayah menjadi beberapa lokasi agar mudah dijangkau oleh seluruh masyarakat kabupaten Karawang. Penelitian ini menggunakan cara pendekatan deskriptif kuantitatif dengan menggunakan sumber data yang digunakan dalam penelitian ini diambil dari website. Website yang digunakan bersumber dari website milik Satgas Covid19 Kabupaten Karawang. Dalam survei ini data yang diambil merupakan data per 18 Juni 2021 dan mencakup 30 kabupaten. Metode K – Means Clustering diolah dengan menggunakan software SPSS 23, dengan asumsi permintaan setiap kecamatan diperkirakan dari angka positif Covid 19 untuk kecamatan tersebut. Hasil penelitian menunjukkan di antaranya cluster 1 beranggotakan 10 kecamatan, cluster 2 terdiri atas 9 kecamatan dan cluster 3 mempunyai anggota 11 kecamatan.